Needlestick and sharps injuries among secondary and tertiary healthcare workers, Saudi Arabia - Anwar M. Makeen; Abdullah A. Alharbi; Mohammed S. Mahfouz; Ahmad Y. Alqassim; Ahmed A. Ismail; Haider M. Arishi; Maged El‐Setouhy; Ronnie D. Horner; Mohammed A. Muaddi (Wiley, 2022)
Abstract Aim The study aimed to assess the incidence of needlestick and sharps injuries among healthcare workers (HCWs) in the Jazan region of Saudi Arabia, as well as to determine whether there exists an association between hospital level and needlestick and sharps injuries rate. Design A cross‐sectional survey was conducted among 609 randomly selected HCWs from nine general hospitals. Methods A self‐administered questionnaire, which covered the structure and process of injection safety, was used for data collection. Results The overall needlestick and sharps injuries incidence rate was 24%. The needlestick and sharps injuries rates were 30% and 14% in secondary and tertiary hospitals, respectively. HCWs working in tertiary hospitals were 61% less likely to have needlestick and sharps injuries than those employed in secondary hospitals. This was mainly the impact of better and continuous training. High safety level maintenance and health education provision are vital in such settings.